Effect of Contour Cultivation on Soil Loss and Yield of Sugarcane - Agarwal, O.P.; singh, Indra Pati (Journal of Soil and Water Conservation, 2022)
Contour cultivation is one of the recogniied method of conservation farming adopted on slopy, cultivated fields for obtaining higher crop yields. Under this practice all field operations like tillage for preparing seed-bed, sowing of crop3, inter cultural operations and irrigation etc. are done at right angles to the slope of land. This practice decreases erosion losses by reducing runoff, and also helps in maintaining better moisture regime of the soil by allowing more and more water to penetrate into the soil on the one hand and distributing the moisture more uniformly in the entire field one the other. The potency of the practice is more intensified when coupled with suitable method of cultivation and it is with his view that an experiment was conducted at the State Soil Conservation Research Demonstration and Training Centre, Rahmankhera, Lucknow during the year 1957-58 to 1960-61.